An introduction to applied semiotics : tools for text and image analysis - Hébert, Louis, 1961- (Routedge, Taylor & Francis Group, 2020)
"An Introduction to Applied Semiotics presents 19 Semiotics tools for text and image analysis. Covering a variety of different schools and approaches, together with the author's own original approach, this is a full and synthetic introduction to Semiotics . This book presents general tools that can be used with any semiotic product. Drawing on the work of Fontanille, Genette, Greimas, Hébert, Jakobson, Peirce, Rastier and Zilberberg, the tools deal with the analysis of themes and action, true and false, positive and negative, rhythm, narration, and other elements. The application of each tool is illustrated with analyses of a wide range of texts and images, from well-known or distinctive literary texts, philosophical or religious texts or images, paintings, advertising and everyday signs and symbols. Each chapter has the same structure: summary, theory, and application, and includes exercises and discussion questions, making it ideal for course use. Covering both visual and textual objects, this is a key text for all courses in semiotics and textual analysis, within linguistics, communication studies, literary theory, design, marketing and related areas"--